Model-Model Pengembangan Kurikulum Bahasa di Sekolah - Sinta Wahyuni; Agustina Agustina; Novia Juita (Departement of Mathematics Education, 2024)
This research aims to investigates models of language curriculum development in schools. Sometimes referred to as library research or librarianship, this study involves the exploration and acquisition of related materials from various sources, such as magazines, books, and articles on a specific issue. The process has been completed. The result of this research is curriculum development, encompassing the planning and design process by the curriculum model developer, along with activities conducted to transform it into teaching and reference materials to achieve national education goals. In designing the curriculum, teachers can choose from several models of Language Curriculum Development in Schools, including the Curriculum Model developed by Robert S. Zais, Peter F. Olivia, Jack Richard, and Graves. It is crucial to examine the strengths and weaknesses of each curriculum development model. The process of developing a language curriculum involves multiple stakeholders, including education administrators, education experts, curriculum experts, science experts, teachers, parents, and community leaders